2019
DOI: 10.1038/s41598-019-53554-y
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound Gaussia luciferase as a tool to track shedding of membrane proteins from the surface of extracellular vesicles

Abstract: Extracellular vesicles (EVs) released by cells play a role in intercellular communication. Reporter and targeting proteins can be modified and exposed on the surface of EVs to investigate their half-life and biodistribution. A characterization of membrane-bound Gaussia luciferase (mbGluc) revealed that its signal was detected also in a form smaller than common EVs (<70 nm). We demonstrated that mbGluc initially exposed on the surface of EVs, likely undergoes proteolytic cleavage and processed fragments of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…The palmitoylation of both cysteines in this sequence at the endoplasmic reticulum-Golgi intermediate compartment drives GAP43 protein to the inner surface of the plasma membrane of growing axons (GAP43 is reviewed in [ 34 ]). Another option for the anchoring of a reporter in the EVs membrane could be the use of a heterologous transmembrane domain, as in the Gaussia luciferase construct reported by [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The palmitoylation of both cysteines in this sequence at the endoplasmic reticulum-Golgi intermediate compartment drives GAP43 protein to the inner surface of the plasma membrane of growing axons (GAP43 is reviewed in [ 34 ]). Another option for the anchoring of a reporter in the EVs membrane could be the use of a heterologous transmembrane domain, as in the Gaussia luciferase construct reported by [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that membranebound Gluc may undergo proteolytic cleavage, leading to the release of protein fragments into the extracellular space in an active form. [147] Following this observation, we developed a novel membrane-bound Gluc based assay to quantitatively track the shedding of membrane proteins from EVs in vitro and in vivo. [147] Furthermore, we utilized this assay to demonstrate that ectodomain shedding in EVs is continuous and mediated by proteases.…”
Section: Indirect Tracking Methodsmentioning
confidence: 99%
“…[147] Following this observation, we developed a novel membrane-bound Gluc based assay to quantitatively track the shedding of membrane proteins from EVs in vitro and in vivo. [147] Furthermore, we utilized this assay to demonstrate that ectodomain shedding in EVs is continuous and mediated by proteases. [147] Takahashi et al took another approach and used lacadherin, a membrane-associated protein often found in EVs, and designed a fusion protein between Gluc and a truncated form of this protein, which labeled cancer cells and their secreted EVs, allowing their in vivo visualization.…”
Section: Indirect Tracking Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been developed for EV preparation, including ultracentrifugation (UC) method [21], filter centrifugation (FC), size exclusion chromatography (SEC) [22,23], affinity purification (AP), immunoprecipitation (IP), sucrose cushion ultracentrifugation (SCU) [24], density gradient centrifugation (DGC), and polymer-based precipitation (PBP) method aka pellet-down method [25]. The SEC method is based on the differential elution profiles of particles of different sizes running through a porous polymer (gel filtration matrix).…”
Section: Introductionmentioning
confidence: 99%